Serum and whole blood calcium and magnesium concentration in postmenopausal women taking oestrogens or oestroprogestins - Bednarek-Tupikowska, Grażyna; Jodkowska, Anna; Antonowicz-Juchniewicz, Jolanta (Menopause Review/Przegląd Menopauzalny, 2007)
Objective: Oestrogen deficiency is a main cause of climacteric syndrome in women. It was investigated whether electrolyte disturbances may also play a role in developing some frequently reported syndromes after menopause and how they change after hormonal therapy. Aim: Controlled clinical study. Materials and methods: Oestrogen, FSH, total serum and whole blood Ca and Mg concentration were measured in 80 healthy postmenopausal women (26 after surgical, 54 after physiological menopause), and in 40 healthy cycling women (control). The investigation was repeated after 4 months of therapy with: oestrogens (ET) in surgical, and oestroprogestins (HT) in natural menopausal women. Statistical analysis was performed. Results: The Mg serum and whole blood concentration in menopausal women was similar to control, and was unchanged after ET/HT. The Ca serum level after menopause was higher than in cycling women; it decreased after therapy and became similar to control. The Ca serum level after HT was significantly higher than after ET. The Ca whole blood concentration after menopause was not significantly increased in comparison to control; it slightly decreased after therapy to a level similar to control. There was no correlation observed between the levels of Ca or Mg and sex steroid hormones. Conclusions: Ca serum and whole blood concentration was higher in menopausal women than in cycling controls and after HT/ET fell to a level similar to controls. The Mg serum and whole blood concentration was similar in menopausal and cycling women; HT/ET did not influence it.